2009
DOI: 10.1189/jlb.0708405
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic zebrafish reporter lines reveal conserved Toll-like receptor signaling potential in embryonic myeloid leukocytes and adult immune cell lineages

Abstract: The immune response of a host to an invading pathogen is dependent on the capacity of its immune cell compartment to recognize highly conserved pathogen components using an ancient class of pattern recognition receptors known as Toll-like receptors (TLRs). Initiation of TLR-mediated signaling results in the induction of proinflammatory cytokines that help govern the scale and duration of any ensuing response. Specificity for TLR signaling is, in part, a result of the differential recruitment of intracellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 78 publications
0
54
0
Order By: Relevance
“…The cadherin-17 (cdh17) gene was chosen because it is highly expressed in all tubule segments. 11 Although a 4.6 kb cdh17 promoter was initially identified, 12 we subsequently found that 1.2 kb of genomic sequence upstream of the start codon is equally sufficient ( Figure 1A). The spatiotemporal expression of this shorter promoter recapitulates the endogenous cdh17 gene expression pattern with eGFP fluorescence/transcripts being detected in all tubule segments from the 8-somite stage to 3 days postfertilization (dpf) (Supplemental Figure 1, A-C).…”
Section: Hnf1b Factors Directly Regulate the Cdh17 Promotermentioning
confidence: 99%
“…The cadherin-17 (cdh17) gene was chosen because it is highly expressed in all tubule segments. 11 Although a 4.6 kb cdh17 promoter was initially identified, 12 we subsequently found that 1.2 kb of genomic sequence upstream of the start codon is equally sufficient ( Figure 1A). The spatiotemporal expression of this shorter promoter recapitulates the endogenous cdh17 gene expression pattern with eGFP fluorescence/transcripts being detected in all tubule segments from the 8-somite stage to 3 days postfertilization (dpf) (Supplemental Figure 1, A-C).…”
Section: Hnf1b Factors Directly Regulate the Cdh17 Promotermentioning
confidence: 99%
“…The zebrafish genome has duplicated tlr genes but only a single copy of myd88 (21,22). We and others have shown that Myd88 functions in zebrafish to modulate innate immune responses to microbes and microbial-associated molecular patterns (MAMPs), such as LPS (23)(24)(25). Notably, LPS sensing in zebrafish differs mechanistically from that in mammals and does not involve a Tlr4-MD2 complex (26).…”
mentioning
confidence: 99%
“…Thus, they are able to sense the same ligands (15)(16)(17), use similar adaptor molecules for signaling (15), and activate the transcription factor NF-κB (13,15,18). In addition, it has been shown that in zebrafish MyD88 modulates innate immune responses to microbes (19)(20)(21)(22).…”
mentioning
confidence: 99%